CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2021)
Cross‐shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross‐shore transport in the shallow (~ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini‐Autonomous Underwater Explorers (M‐AUEs). The M‐AUEs were programmed to maintain a specified depth, and were deployed near a mooring. Transport of the M‐AUEs was predominantly onshore, with average velocities up to 14 cm s −1 . To put the M‐AUE deployments into a broader context, we simulated > 500 individual high‐frequency internal waves observed at the mooring over a 14‐d deployment; in each internal wave, we released both depth‐keeping and passive virtual larvae every meter in the vertical. After the waves' passage, depth‐keeping virtual larvae were usually found closer to shore than passive larvae released at the same depth. Near the top of the water column (3–5‐m depth), ~ 20% of internal waves enhanced onshore transport of depth‐keeping virtual larvae by ≥ 50 m, whereas only 1% of waves gave similar enhancements to passive larvae. Our observations and simulations showed that depth‐keeping behavior in high‐frequency internal waves resulted in enhanced onshore transport at the top of the water column, and reduced offshore dispersal at the bottom, compared to being passive. Thus, even weak depth‐keeping may allow larvae to reach nearshore adult habitats more reliably than drifting passively.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

A novel cross‐shore transport mechanism revealed by subsurface, robotic larval mimics: Internal wave deformation of the background velocity field - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Matthew H. Alford; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2020)
Coastal physical processes are essential for the cross‐shore transport of meroplanktonic larvae to their benthic adult habitats. To investigate these processes, we released a swarm of novel, trackable, subsurface vehicles, the Mini‐Autonomous Underwater Explorers (M‐AUEs), which we programmed to mimic larval depth‐keeping behavior. The M‐AUE swarm measured a sudden net onshore transport of 30–70 m over 15–20 min, which we investigated in detail. Here, we describe a novel transport mechanism of depth‐keeping plankton revealed by these observations. In situ measurements and models showed that, as a weakly nonlinear internal wave propagated through the swarm, it deformed surface‐intensified, along‐isopycnal background velocities downward, accelerating depth‐keeping organisms onshore. These higher velocities increased both the depth‐keepers' residence time in the wave and total cross‐shore displacement, leading to wave‐induced transports twice those of fully Lagrangian organisms and four times those associated with the unperturbed background currents. Our analyses also show that integrating velocity time series from virtual larvae or mimics moving with the flow yields both larger and more accurate transport estimates than integrating velocity time series obtained at a point (Eulerian). The increased cross‐shore transport of organisms capable of vertical swimming in this wave/background‐current system is mathematically analogous to the increase in onshore transport associated with horizontal swimming in highly nonlinear internal waves. However, the mechanism described here requires much weaker swimming speeds (mm s −1 vs. cm s −1 ) to achieve significant onshore transports, and meroplanktonic larvae only need to orient themselves vertically, not horizontally.

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Salbutamol effects on systemic potassium dynamics during and following intense continuous and intermittent exercise - Muath M. Altarawneh; Aaron Petersen; Robert Smith; David M. Rouffet; Francois Billaut; Ben D. Perry; Victoria L. Wyckelsma; Antony Tobin; Michael J. McKenna (European Journal of Applied Physiology, 2016)

A genetic discontinuity in moose (Alces alces) in Alaska corresponds with fenced transportation infrastructure - Robert E. Wilson; Sean D. Farley; Thomas J. McDonough; Sandra L. Talbot; Perry S. Barboza (Conservation Genetics, 2015)

The Y ersinia pestis HmsCDE regulatory system is essential for blockage of the oriental rat flea ( X enopsylla cheopis ), a classic plague vector - Alexander G. Bobrov; Olga Kirillina; Viveka Vadyvaloo; Benjamin J. Koestler; Angela K. Hinz; Dietrich Mack; Christopher M. Waters; Robert D. Perry (Environmental Microbiology, 2015)
Summary The second messenger molecule cyclic diguanylate is essential for Y ersinia pestis biofilm formation that is important for blockage‐dependent plague transmission from fleas to mammals. Two diguanylate cyclases ( DGCs ) HmsT and Y 3730 ( HmsD ) are responsible for biofilm formation in vitro and biofilm‐dependent blockage in the oriental rat flea X enopsylla cheopis respectively. Here, we have identified a tripartite signalling system encoded by the y3729‐y3731 operon that is responsible for regulation of biofilm formation in different environments. We present genetic evidence that a putative inner membrane‐anchored protein with a large periplasmic domain Y 3729 ( HmsC ) inhibits HmsD DGC activity in vitro while an outer membrane P al‐like putative lipoprotein Y 3731 ( HmsE ) counteracts HmsC to activate HmsD in the gut of X . cheopis . We propose that HmsE is a critical element in the transduction of environmental signal(s) required for HmsD ‐dependent biofilm formation.

Establishing a reference group for distal 18q-: clinical description and molecular basis - Jannine D. Cody; Minire Hasi; Bridgette Soileau; Patricia Heard; Erika Carter; Courtney Sebold; Louise O’Donnell; Brian Perry; Robert F. Stratton; Daniel E. Hale (Human Genetics, 2014)

Polyamines are required for the expression of key Hms proteins important for Yersinia pestis biofilm formation - Brian W. Wortham; Marcos A. Oliveira; Jacqueline D. Fetherston; Robert D. Perry (Environmental Microbiology, 2010)
Summary We previously showed that mutations in the genes encoding the two main biosynthetic enzymes responsible for polyamine production, arginine decarboxylase (SpeA) and ornithine decarboxylase (SpeC) cause a loss of biofilm formation in Yersinia pestis . In Y. pestis the development of a biofilm is dependent on 6 Hms (hemin storage) proteins (HmsH, F, R, S, T and P) grouped into 3 operons; hmsHFRS , hmsT and hmsP . In this article we show that polyamines are necessary to maintain the levels of key Hms proteins. In the absence of polyamines there is an ∼93%, ∼43% and ∼90% reduction in protein levels of HmsR, HmsS and HmsT respectively. Overexpression of hmsR and hmsT from plasmids alone can restore biofilm formation to a SpeA ‐ SpeC ‐ mutant. Addition of exogenous putrescine also restores normal levels of HmsR, HmsS, HmsT and biofilm production. Analyses using transcriptional reporters and quantitative RT‐PCR indicate that the initiation of transcription and mRNA stability are not reduced by polyamine deficiency. Instead, translational reporters indicate that polyamines function at least in part by modulating the translation of HmsR and HmsT. Although construction of a consensus Shine–Dalgarno sequence upstream of hmsT modestly reduced the stimulation of translation by putrescine, additional mechanisms likely contribute to the polyamine‐dependent expression of HmsT. Finally, we have shown that polyamines play a role in bubonic plague.

Yersinia ironomics: comparison of iron transporters among Yersinia pestis biotypes and its nearest neighbor, Yersinia pseudotuberculosis - Stanislav Forman; James T. Paulley; Jacqueline D. Fetherston; Yi-Qiang Cheng; Robert D. Perry (BioMetals, 2010)

Effects of 14 days of microgravity on fast hindlimb and diaphragm muscles of the rat - Mark D. Schuenke; David W. Reed; William J. Kraemer; Robert S. Staron; Jeff S. Volek; Wesley C. Hymer; Scott Gordon; L. Perry Koziris (European Journal of Applied Physiology, 2009)

Insights into Yersinia pestis biofilm development: topology and co‐interaction of Hms inner membrane proteins involved in exopolysaccharide production - Alexander G. Bobrov; Olga Kirillina; Stanislav Forman; Dietrich Mack; Robert D. Perry (Environmental Microbiology, 2008)
Summary Primarily, three operons, hmsHFRS, hmsT and hmsP , are responsible for the development of a Yersinia pestis biofilm, which is essential for blockage‐dependent transmission of plague from fleas to mammals. Here, using specific antibodies, a polymeric β‐1,6‐ N ‐acetyl‐ d ‐glucosamine‐like polysaccharide was detected in the extracellular matrix of hmsHFRS ‐dependent Y. pestis biofilm. The production of this exopolysaccharide (EPS) was controlled by diguanylate cyclase HmsT and EAL domain phosphodiesterase HmsP, acting as positive and negative regulators respectively. Cellular compartmentalization of soluble segments of Hms inner membrane proteins, including the putative glycosyltransferase domain of HmsR, the diguanylate cyclase/GGDEF domain of HmsT and the phosphodiesterase/EAL domain of HmsP, was determined by a combination of topology prediction algorithms and construction of C‐terminal translational fusions with β‐galactosidase and alkaline phosphatase. Multiple interactions of Hms inner membrane proteins were detected using bacterial cAMP based two‐hybrid system. Biochemical analyses confirmed some of these protein–protein interactions. Our results indicate that synthesis and regulation of the Y. pestis biofilm EPS occurs in the cytoplasm by a proposed Hms enzymatic complex.

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

Roles of the Yfe and Feo transporters of Yersinia pestis in iron uptake and intracellular growth - Robert D. Perry; Ildefonso Mier; Jacqueline D. Fetherston (BioMetals, 2007)

Adventiously-bound redox active iron and copper are at the center of oxidative damage in Alzheimer disease - George Perry; Marta A. Taddeo; Robert B. Petersen; Rudy J. Castellani; Peggy L.R. Harris; Sandra L. Siedlak; Adam D. Cash; Quan Liu; Akohiko Nunomura; Craig S. Atwood; Mark A. Smith (BioMetals, 2003)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)